In vitro and in vivo antiplasmodial activity of extracts and isolated constituents of Alstonia congensis root bark. (5th October 2019) - Cimanga, R. Kanyanga; Nsaka, S. Lumpu; Tshodi, M. Ehata; Mbamu, B. Maya; Kikweta, C. Munduku; Makila, F. Bool-Miting; Cos, Paul; Maes, Louis; Vlietinck, Arnold J.; Exarchou, Vassiliki; Tuenter, Emmy; Pieters, Luc
Abstract: Ethnopharmacological relevance: An aqueous decoction of root bark of Alstonia congensis Engl. (Apocynaceae) is used in several African countries to treat various ailments including malaria. Materials and methods: Extracts of different polarity and isolated constituents were tested in vitro for their antiplasmodial activity against the chloroquine-resistant strain Plasmodium falciparum K1 and the chloroquine-sensitive strain P. falciparum NF54A19A, as well as for their cytotoxic effects againt MRC-5 cells (human lung fibroblasts). Extracts and fractions were evaluated in vivo against the chloroquine-resistant strain P. yoelii N67 and the chloroquine-sensitive strain P. berghei berghei ANKA. Results: The aqueous extract, the 80% methanol extract and the alkaloid-enriched extract exhibited strong antiplasmodial activity against P. falciparum K1 with IC50 values < 10 µg/ml and against P. falciparum NF54 A19A with IC50 values < 0.02 µg/ml. In vivo against P. yoelii N67, at the highest oral dose of 400 mg/kg body weight, all extracts produced 70–73% chemosuppression, while against P. berghei berghei, more than 75% chemosuppression was observed. With regard to the isolated constituents, boonein was inactive in vitro against P. falciparum K-1 (IC50 > 64 µM), while echitamine, 6, 7-seco-angustilobine B and β-amyrin exhibited moderate activity (IC50 < 30 µM). Against P. falciparum NF54 A19A, boonein was inactive (IC50 > 64 µM), while echitamine, 6, 7-secoangustilobine and β-amyrin showed moderate IC50 values of 11.07, 21.26 and 40.70 µM, respectively. Conclusion: These results demonstrated that all extracts from A. congensis root bark possessed antiplasmodial activity in vitro and in vivo . They can be used as raw materials for the preparation of ameliorated remedies for the treatment of uncomplicated malaria. The observed antiplasmodial activity may be due in part to the presence of indole alkaloids. Graphical abstract: fx1